African cities alternative visions of urban theory and practice - Myers, Garth Andrew (New York Zed Books Ltd, 2011)
As African societies come to live more and more in cities, they do so in ways that challenge prevailing theories and models of urban development in geography, sociology, anthropology, and planning. This book uses African urban concepts and experiences to speak back to theoretical and practical concerns in urban studies and disciplines that study cities, as well as in African studies. It argues for a re-vision a seeing again, and a revising of how cities in Africa are discussed and written about in both urban studies and African studies. Cities in Africa still are either ignored, banished to a different, other, lesser category of not-quite cities, or held up as examples of all that can go wrong with urbanism in much of both the mainstream and even critical urban literature. This book encourages African studies and urban studies scholars across the world to engage with the vibrancy and complexity of African cities with fresh eyes. It uses the author's own research and a close reading of works by other scholars, writers, and artists on a broad range of sixteen cities in Africa to highlight six themes that help illuminate what is happening in and across the region's cities.
Includes bibliographical references (p. [199]-232) and index.
Keywords: Cities and towns -Africa.